Decitabine in combination with donor lymphocyte infusions can induce remissions in relapsed myeloid malignancies with higher leukemic burden after allogeneic hematopoietic cell transplantation. (September 2018) - Sommer, Sebastian; Cruijsen, Marjan; Claus, Rainer; Bertz, Hartmut; Wäsch, Ralph; Marks, Reinhard; Zeiser, Robert; Bogatyreva, Lioudmila; Blijlevens, Nicole M.A.; May, Annette; Duyster, Justus; Huls, Gerwin; et al.
Highlights: 26 patients with overt hematological relapse after allo-HCT were evaluable. DAC + DLI proved feasible and effective in relapse after allo-HCT. Overall response rate 19% (CR/CRi (4/26); PR (1/26)), stable disease in 54% (14/26). Median overall survival was 4.7 months. Abstract: The combination of 5-azacytidine (AZA) with donor lymphocyte infusions (DLIs) can induce remissions in patients with relapsed myeloid malignancies after allo-HCT. As decitabine (DAC) is known to be effective also in AML/MDS with leukocytosis, we investigated the combination of DAC with DLIs for relapse after allo-HCT. Between 2006 and 2016, 26 patients (median age 59 years) with AML (n = 18), MDS (n = 6), or MPN (n = 2) and overt hematological relapse after allo-HCT were treated. Median duration from allo-HCT to relapse was 306 days (range, 76–4943). Eighteen patients received DAC + DLIs, 8 DAC-only (median number cycles of DAC: 2, range 1–13, median number of DLIs: 2, range 1–10). The incidence of acute and chronic GvHD in patients receiving DLI was 17% (3/18) and 6% (1/18), respectively. CR/CRi was achieved in 15% (4/26), PR in 4% (1/26), and stable disease in 58% (15/26) of patients. Eight patients received a second allo-HCT. Median overall survival was 4.7 months. Elevated PD-L1 protein expression in bone marrow cells was detected in 4/8 patients with >20% blast infiltration prior to DAC, without a clear association with response. In conclusion, the DAC + DLI regimen proved feasible and effective in relapsed myeloid malignancies after allo-HCT, with efficacy not restricted to patients with low leukemic burden.